Eyeing opthalmic products: Bioequivalence assessment and drug development - Strategic considerations - AJP, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
The use of pharmacodyamic endpoints has been reported to assess the bioequivalence of two ophthalmic formulations of ketotifen.[1] The authors published a well designed and executed study, which, among other things,included appropriate and a priori defined pharmacodynamic endpoints in the targeted patient population.[1] The applied bioequivalence strategy of using pharmacodynamic markers (but not pharmacokinetics) was adequately justified because of the lack of quantifiable levels of ketotifen in the systemic circulation after ocular administration.